(untitled) (International Journal of Ayurveda and Pharma Research, 2022)
Nasal Polyposis (NP) is not simply mucosa oedema, but rather grape shaped, smooth, soft, freely mobile mucosal swellings that are often visible on anterior rhinoscopy. Polyps arise from the lateral wall of nose. NP may be present without clinically significant sinus disease and vice versa. In Ayurveda, polyposis can be understood with Nasa Arsha. Modern management includes antibiotic, systemic and topical corticosteroids, decongestants and surgery. And lot of chances for recurrence after surgery especially in Ethmoidal polyps. In Ayurveda, various treatment modalities have been proposed for the treatment of Arsha as Shastra karma (operative procedure), Kshara karma (applying some alkaline drugs), Agni karma (cauterization) and Bhaishaja (conservative/medical treatment). The reported case revealed that B/L ethmoidal polyps are high recurrence rate after surgery and can be managed with Ayurvedic medicine to give sustained relief from symptoms.